Diseño de una micro-red basada en energía solar fotovoltaica y la factibilidad técnico – económica para su implementación en los sectores rurales y urbano marginales del Cantón “Quevedo – Sector 024”. - Puente Bosquez, Samantha Marlene (2022)
This research aims to design a micro - grid based on photovoltaic solar energy for its supply in a marginal urban area, specifically aimed at the concept of micro - grids, basically being small systems with a fusion of energy technology renewables and the technology of conventional energy systems. The research focused on the theoretical criteria of photovoltaic solar energy, current advantages and disadvantages. Consequently, the data collection and processing process was carried out, based on a meteorological station, the same one that provides data on monthly solar radiation, temperature, among others; the same one in which the maximum and minimum historical temperature was obtained (19.8 ºC and 26.2 ºC respectively). Subsequently, the data to select and obtain the number of modules and inverter was entered into the PVsyst software. It was also evaluated economically using the indicators of the NPV (Net Present Value) of - $ 11,659.34 and the IRR (Internal Rate of Return) with -2%, as well as the recovery time, they were negative, the electricity distribution networks is the most economical and viable option to carry out in rural, urban - marginal sectors.